Method Of Teaching English Used At SMP Unggulan Nawa Kartika (Islamic Boarding School) In 2012 / 2013 Academic Year: A Micro Ethnography Research - Isnaini, Diana; , Prof. Dr. Hj. Endang Fauziati, M.Hum; , Dra. Dwi haryanti, M.Hum (2013)
This research paper focuses on the method of teaching English and describes it implemented at the second year of SMP Unggulan Nawa Kartika. Objectives of this research are to describe (1) method of the teaching English at SMP Unggulan Nawa Kartika, (2) the design used of the teaching English which is includes a) the learning objective, b) the teacher's roles and the learner's roles, c) the classroom activities, d) the materials, e) and media, (3) the strengths and weaknesses of the method in teaching English. This study is a micro ethnography research. The data in this study is all of behavior between the teacher and the students in English teaching learning process at the second year of SMP Unggulan Nawa Kartika. The object of this research is the method applied by the teacher in English teaching learning process. The subject of this research is all of second year students, especially of 8B class that consists of 24 female students. The data analyzed by a micro ethnography research in describing of the teacher's and the students' behavior or attitudes. Based on the observation from February until April, the writer knows that the teacher demonstrates of three appropriate methods applied by the teacher in English teaching learning activity at SMP Unggulan Nawa Kartika. These methods are Grammar Translation Method (GTM), Communicative Language teaching (CLT), and Genre-Based Approach (GBA). In every each method has learning objectives to the students. In Grammar Translation Method (GTM), the objective is to increase the students' language skills in reading and writing by providing a text and explaining with mother tongue. In Communicative Language Teaching (CLT), the objective is to build up the students' communication in real interaction by giving simple conversation and four language skills to the students. In Genre-Based Approach (GBA), the objective is to develop the students' writing skill by using some of genres or text types.